1984
DOI: 10.1121/1.391006
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual reality of tone chroma in early infancy

Abstract: It has often been advanced that pitch is a two-dimensional perceptual attribute, its two dimensions being: (1) tone height, a perceptual quality monotonically related to frequency; and (2) tone chroma, a quality shared by tones forming an octave interval. However, given that many musically uneducated adults do not seem to perceive tone chroma, this model is controversial. We investigated the sensitivity of three-month-old infants to tone chroma by means of a behavioral habituation-dishabituation procedure. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 0 publications
3
74
1
Order By: Relevance
“…These findings together with earlier research indicate a clear developmental progression, beginning with effects of perfect fifth and octave intervals in the first year of life (Demany & Armand, 1984;Trainor & Trehub, 1993a, 1993b, and followed by effects of key membership by 5 years of age and implied harmony by 7 years of age. Implicit knowledge about key membership, although absent in 8-month-olds (Trainor & Trehub, 1992), is likely to be present well before 5 years of age, which is the youngest age that has been examined postinfancy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These findings together with earlier research indicate a clear developmental progression, beginning with effects of perfect fifth and octave intervals in the first year of life (Demany & Armand, 1984;Trainor & Trehub, 1993a, 1993b, and followed by effects of key membership by 5 years of age and implied harmony by 7 years of age. Implicit knowledge about key membership, although absent in 8-month-olds (Trainor & Trehub, 1992), is likely to be present well before 5 years of age, which is the youngest age that has been examined postinfancy.…”
Section: Discussionmentioning
confidence: 79%
“…Tones that are one octave apart (i.e., fundamental frequencies standing in a 1:2 ratio) sound very similar in musical contexts, are functionally equivalent, and are often assigned the same note name. Moreover, research with very young infants indicates that even they perceive the similarity of tones that are one octave apart (Demany & Armand, 1984). Another near-universal is the use of a small set of discrete pitches per octave (scales) and their repetition in successive octaves.…”
mentioning
confidence: 99%
“…Nevertheless, the results provide little support for the claim that ratio simplicity is an important factor in perceptual processing. For example, evidence of octave equivalence has been absent in some instances (Kallman, 1982) and restricted to highly trained listeners in others (Allen, 1967; see also Thurlow & Erchul, 1977), which is at odds with the evidence of octave equivalence in infancy (Demany & Armand, 1984). Moreover, Burns and Ward (1978, Experiment 4) reported no evidence for natural categories of intervals based on the simplicity of frequency ratios.…”
mentioning
confidence: 98%
“…tones an octave apart (frequency ratio of2:1) is universal (Dowling & Harwood, 1986;Lerdahl & Jackendoff, 1983), being apparent in infants as young as 3 months of age (Demany & Armand, 1984). Octaves are unique, however, in that tones an octave apart have the same tone chroma (i.e., the distinction between any tone called X and any tone called Y) as well as the simplest frequency ratio of any interval (other than a unison).…”
mentioning
confidence: 99%
“…This study, therefore, shows that infants are like adults in perceiving equality between octaves. 11 Much research suggests that newborns as well as older infants identify a speaker from the unique complex of pitches in the individual voice as well as from the intonation (called prosody) or rising and falling contours of the pitches in a spoken phrase. 10 Eimas et al 12 showed in 1971 that infants are able at birth to perceive some of the complex frequencies inherent in phonetic showed that infants within a day of birth could identify the individual characteristics of their mother's voice having only heard the low frequency components of it from inside the womb.…”
Section: Newborn Hearing Behaviors Indicating Hearing In the Newborǹ`cmentioning
confidence: 99%